Comportamento de fluência e tração a quente do aço inoxidável austenítico AISI 201LN - Pelissari, Gustavo Henrique (2020)
Among the different stainless steel (SS) series, the 200 series, also known as Cr-Ni-Mn alloys, has recently been gaining prominence worldwide. In spite of that, studies addressing the high-temperature deformation these alloys are still scarce in the literature. In this context, this study aims to assess the mechanical and microstructural behavior under deformation of the AISI 201LN alloy when subjected to creep and hot tensile tests. The material was microstructurally characterized as received and after heat treatment. The tensile tests were conducted at room temperature and in the range of 500-800 °C under an initial deformation rate of 10-3s-1, whereas the creep tests were performed under constant load in the temperature range of 600-800 °C. Comparison between the results obtained for the AISI 201 LN alloy and those for other 300 series traditional materials showed very similar values. After the tensile tests at room temperature, a mostly martensitic microstructure, caused by transformation induced plasticity (TRIP), was observed. After the creep tests, evidence of precipitation of Cr carbides was observed in the grain boundaries of some specimens. The long period of exposure to high temperatures changed the morphology of the δ ferrite islands, indicating decomposition of this phase. In the tests performed at 800 °C, formation of precipitates rich in N was observed on the surface of specimens, in addition to intense deterioration of their microstructure. Overall, fracture surface analysis of the specimens indicated a gradually greater predominance of ductile fracture in the tests at higher temperatures. Based on the Zener-Hollomon parameter, constitutive equations were proposed to describe the creep behavior of the material within the range of stresses and temperatures employed. The Larson-Miller creep parameterization technique was applied to the experimental data set aiming to extrapolate from the creep results.